The Development of Learning Media using Wordwall Application in Social Science Learning - Hanny Maulida Rahma; Tita Mulyati; Yona Wahyuningsih (International Journal of Learning and Instruction (IJLI), 2022)
This research is stimulated by optimizing the material for cultural diversity of traditional houses in Indonesia in the fourth grade of elementary school in social science learning through the digital media of the Wordwall web application. The use of learning media that can add students' interest in learning in social science learning in elementary schools as well as decreasing students' awareness in preserving culture. This research has mission to produce a product in the form of a Wordwall web application learning media on social science material for fourth grade of elementary school. This research used the development of D&D (Design and Development) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The instrument used is a questionnaire to validate material experts, linguists and media experts, as well as teacher and student responses. This research produces a product in the form of learning media for the Wordwall web application material for cultural diversity of traditional houses in Indonesia. Based on the results of the feasibility test through validation by experts, namely material experts, linguists, and media experts using a validation questionnaire, they obtained a "Excellent" score category with indicators of presentation feasibility, language, usability, and illustration design (content). Likewise, the responses of teachers and students also acquire an average of 90.3% in the classify of "Excellent" scores with indicators of material content, presentation, language, and design quality. Therefore, the development of Wordwall application learning media in social science subject theme 7, the beauty of diversity in my country has become one of the optimizations of learning media.Â Keywords: Wordwall Application, Learning Media, social science learning in Elementary SchoolÂ